The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/14614448221099172
|View full text |Cite
|
Sign up to set email alerts
|

Self-representations of the experience of anorexia on YouTube: The joint influence of the explanatory model and the web platform

Abstract: This study analyzes the self-representations of Russian-speaking women with anorexia on YouTube. Using multimodal interaction analysis, the research focuses on how the explanatory model of anorexia and the representation platform influence the narratives produced by vloggers who have experienced or are experiencing anorexia. It is concluded that anorexia is mainly represented in these videos as a weight-related mental health disorder. Although the explanatory model of anorexia shapes self-representations on Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…In this study, it was found that the majority of the videos 47 (79.66%) discussed the symptoms of anorexia nervosa and 48 (81.36%) of the videos focused on treatment. The presence of vloggers and people who have experienced anorexia nervosa firsthand has helped others with the recognition of this disorder [10]. Hence, social media platforms play an important role in creating awareness of diseases, especially related to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that the majority of the videos 47 (79.66%) discussed the symptoms of anorexia nervosa and 48 (81.36%) of the videos focused on treatment. The presence of vloggers and people who have experienced anorexia nervosa firsthand has helped others with the recognition of this disorder [10]. Hence, social media platforms play an important role in creating awareness of diseases, especially related to mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this platform may be one of the most important sources of knowledge on mental health for this age group. Depression is one of many mental health conditions that is portrayed on Russian-language YouTube (Mikhaylova, 2022). The topic of mental health topic has already become trendy in this digital space in Russia over approximately the last 5 years.…”
Section: Youtube’s Censorship Policies and The Importance Of This Pla...mentioning
confidence: 99%